Chromosome 19 rearrangements in ovarian carcinomas: Zinc finger genes are particularly targeted. Issue 7 (14th March 2014) - Smebye, Marianne L.; Sveen, Anita; Haugom, Lisbeth; Davidson, Ben; Tropé, Claes G.; Lothe, Ragnhild A.; Heim, Sverre; Skotheim, Rolf I.; Micci, Francesca
<x xml:space="preserve">Abstract</x> Chromosome 19 is frequently rearranged in ovarian carcinomas, but the pathogenetic consequences of this are not clearly understood. We performed microarray gene expression analysis on 12 ovarian carcinomas that carry a rearranged chromosome 19 in their karyotype. These aberrant chromosomes have previously been microdissected and analyzed by array‐based CGH. In the current study, we wanted to explore whether the genomic alterations thus detected correlated with changes in gene expression. The microarray gene expression analysis gave information on 407 genes mapping in gained genomic regions on chromosome 19, of which 92 showed association between DNA gain and upregulated expression. Of the genes showing this association, 39 (42%) showed gain in at least two samples. The majority of these 39 genes of interest (n = 24, 62%) encode zinc finger proteins, which otherwise make up only 15% of the approximately 1, 400 genes on chromosome 19. The strongest association was found for ZNF223 which was upregulated in samples with genomic gain compared with samples without gain. We suggest that DNA copy number changes brought about by rearrangements of chromosome 19 contribute to ovarian carcinogenesis by leading to upregulation of ZNF223 and other zinc finger genes. © 2014 Wiley Periodicals, Inc.